Effects of lower-limb muscular fatigue on stair gait. Issue 15 (26th November 2015) - Qu, Xingda
Abstract: The objective of the present study was to determine the effects of lower-limb muscular fatigue on stair gait. Twelve healthy young male adults between 20 and 30 years old participated in the experiment. There were two experimental sessions corresponding to a no fatigue condition and a lower-limb muscular fatigue condition, respectively. Lower-limb muscular fatigue was induced using repetitive lower-limb pushing exertions. Both ascent and descent were studied. Stair gait was assessed by lower-limb joints and trunk kinematics, and postural stability measures. It was found that lower-limb muscular fatigue compromised stair gait during descent, but did not make any difference during ascent. These findings highlighted the importance of minimizing exposures to lower-limb muscular fatigue during descent in stair accident prevention.